The role of product quality, promotion, conformity in increasing consumer loyalty - Sukaris Sukaris; Novita Tri Yulia (INNOVATION RESEARCH JOURNAL, 2021)
Currently, business competition is getting more competitive. Companies must act to improve and maintain product quality. Product quality is the ability of a product to meet customer needs and consumers. Product quality can be a company's mainstay so that its products are able to compete in its market segments with similar products. Quality will encourage consumers to establish close relationships with the company for a long time which in turn creates consumer loyalty. This study aims to determine the effect of product quality, promotion and conformity on consumer loyalty at the "X" fast food restaurant in Gresik Regency. The sample used in this study were 100 young respondents using the method of accidental sampling. The types and sources of data used are primary data in the form of questionnaire answers from respondents. Tests were carried out using SPSS. The results of this study indicate that product quality, promotion and conformity have a positive and significant effect on consumer loyalty.